Gene Expression Analyses of Arabidopsis Chromosome 2 Using a Genomic DNA Amplicon Microarray - Kim, Heenam; Snesrud, Erik C.; Haas, Brian; Cheung, Foo; Town, Christopher D.; Quackenbush, John (Genome Research, 2003)
The gene predictions and accompanying functional assignments resulting from the sequencing and annotation of a genome represent hypotheses that can be tested and used to develop a more complete understanding of the organism and its biology. In the model plantArabidopsis thaliana, we developed a novel approach to constructing whole-genome microarrays based on PCR amplification of the 3′ ends of each predicted gene from genomic DNA, and constructed an array representing more than 94% of the predicted genes and pseudogenes on chromosome 2. With this array, we examined various tissues and physiological conditions, providing expression-based validation for 84% of the gene predictions and providing clues as to the functions of many predicted genes. Further, by examining the distribution of expression along the physical chromosome, we were able to identify a region of repressed transcription that may represent a previously undescribed heterochromatic region.[The sequence data from this study have been submitted to ArrayExpress under accession nos.: For the Array Design, A-TIGR-2. For the three subgroups of experiments: AbioticStress, E-TIGR-2; BioticStress, E-TIGR-3; Tissues, E-TIGR-4.]